Enhancing sustainability: Polyvinyl alcohol bioplastic reinforced with cassava starch and eggshell - Rahman, A. U.; L., Mohd Zaki; Siti Maznah, Kabeb (AIP Publishing, 2024)
Present study focuses on enhancing the mechanical strength and biodegradability of polyvinyl alcohol (PVA) bioplastic films by incorporating cassava starch (CS) and eggshell (ES) fillers, addressing environmental concerns associated with traditional plastic packaging. The study investigated the effect of filler concentrations (1, 3 and 5 wt. %) on the mechanical properties and biodegradability of the developed bioplastic films. Characterization methods including Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) analysis were employed, along with mechanical testing, biodegradability assessment, water uptake analysis, and evaluation of water vapor transmission rate (WVTR). The results demonstrate that increasing biofiller loading enhances the biodegradability of PVA bioplastic films, particularly evident at 5 wt. % CS and ES, which exhibit the highest weight loss. PVA films with ES exhibit greater susceptibility to degradation than those filled with CS, showing a ~4% difference at 5 wt.% loading. The water uptake results contradict the biodegradability findings, as PVA bioplastic containing CS shows the highest water uptake despite exhibiting lower biodegradability. Furthermore, the PVA bioplastic film with 5 wt. % CS exhibited the highest WVTR at 11.52%, surpassing ES at a similar weight loading. The findings reveal that incorporating a 5 wt.% biofiller loading significantly enhances tensile strength by approximately 136.9% and 109.7% for PVA_CS5 (29.66 MPa) and PVA_ES5 (26.26 MPa), respectively, compared to neat PVA bioplastic film (12.52 MPa), indicating the effectiveness of biofiller as a reinforcing agent. The FTIR analysis reveals structural changes in PVA bioplastic films, with disrupted hydrogen bonds within molecules particularly for CS-filled films, potentially enhancing mechanical properties.SEM analysis provided further evidence of the uniform dispersion of CS and ES within the PVA matrix, supporting enhanced interfacial adhesion and thereby improving mechanical properties.